Contrasting the Social Cognitive and Metacognitive Capacities Among Patients With Schizophrenia and Autism Spectrum Disorders Enrolled in Psychiatric Rehabilitation. Issue 10 (14th October 2022) - Dubreucq, Julien; Martin, Aude; Gabayet, Franck; Plasse, Julien; Wiesepape, Courtney; Quilès, Clélia; Verdoux, Hélène; Franck, Nicolas; Lysaker, Paul H.
Abstract: Unique deficits in synthetic metacognition have been found in schizophrenia when compared with other psychiatric conditions and community controls. Although persons with autism spectrum disorders (ASD) display similar deficits in social cognition relative to those with schizophrenia, to date no study has compared metacognitive function between these groups. We aimed to compare the metacognitive capacities of persons with schizophrenia and ASD and their associations with other outcomes (neurocognition, social cognition, depression, and quality of life). Fifty-six outpatients with schizophrenia or ASD (mean age, 32.50 [9.05]; 67.9% male) were recruited from two French Centers of Reference for Psychiatric Rehabilitation of the REHABase cohort. Evaluation included the Indiana Psychiatric Illness Interview, Metacognition Assessment Scale–Abbreviated, Movie for the Assessment of Social Cognition, and a large cognitive battery. Compared with those with schizophrenia, participants with ASD had higher self-reflectivity ( p = 0.025; odds ratio, 1.38 [1.05–1.86]) in univariable analyses. Metacognitive deficits may be found in ASD with a profile that varies from what is found in schizophrenia. It is possible that methods for enhancing metacognitive abilities during psychiatric rehabilitation may be refined to assist adults with ASD to better manage their own recovery.